Bayesian Analysis for Remote Biosignature Identification on exoEarths (BARBIE). II. Using Grid-based Nested Sampling in Coronagraphy Observation Simulations for O2 and O3 - Natasha Latouf; Avi M. Mandell; Geronimo L. Villanueva; Michael D. Himes; Michael Dane Moore; Nicholas Susemiehl; Jaime Crouse; Shawn Domagal-Goldman; Giada Arney; Vincent Kofman; Amber V. Young (The Astronomical Journal, 2023)
We present the results for the detectability of the O _2 and O _3 molecular species in the atmosphere of an Earth-like planet using reflected light at visible wavelengths. By quantifying the detectability as a function of the signal-to-noise ratio (S/N), we can constrain the best methods to detect these biosignatures with next-generation telescopes designed for high-contrast coronagraphy. Using 25 bandpasses between 0.515 and 1 μ m and a preconstructed grid of geometric albedo spectra, we examined the spectral sensitivity needed to detect these species for a range of molecular abundances. We first replicate a modern-Earth twin atmosphere to study the detectability of current O _2 and O _3 levels, and then expand to a wider range of literature-driven abundances for each molecule. We constrain the optimal 20%, 30%, and 40% bandpasses based on the effective S/N of the data, and define the requirements for the possibility of simultaneous molecular detection. We present our findings of O _2 and O _3 detectability as functions of the S/N, wavelength, and abundance, and discuss how to use these results for optimizing future instrument designs. We find that O _2 is detectable between 0.64 and 0.83 μ m with moderate-S/N data for abundances near that of modern Earth and greater, but undetectable for lower abundances consistent with a Proterozoic Earth. O _3 is detectable only at very high S/N data in the case of modern-Earth abundances; however, it is detectable at low-S/N data for higher O _3 abundances that can occur from efficient abiotic O _3 production mechanisms.